INVESTMENT MANAGEMENT LECTURE, CAPITAL MARKET TRAINING AND INVESTMENT STUDENTS INTEREST: COMBINATION OF CAPITAL MARKET THEORY AND PRACTICE - Gregorius Paulus Tahu, G. Oka Warmana, Wayan Widnyana (International Journal of Advanced Science and Technology, 2020)
The purpose of this study was to examine the effect of investment management lectures andcapital market training on the interest of students investing in the capital market. This study took asample of students from the Faculty of Economics and Business management study program atMahasaraswati University Denpasar. The analytical tool used is multiple regression. From the testresults it can be concluded that students who have taken investment management lectures have ahigher interest in investing in the capital market than students who have not taken investmentmanagement lectures. Students who have participated in capital market training also show highinterest in investing in the capital market.